Introduction of Exotic Conifers in Himachal Pradesh - Gupta, G. C. (Indian Forester, 1969)
Results of trials of exotic conifers carried out since 1902 by various workers indicate that Mexican pines are suitable for introduction in Himachal Pradesh. Pinus patula, Larix leptolepis, Thuja plicata, Pinus hartwegii, Pinus syivestris, Cupressus arizonica, PseudoJuga taxifolia and Pinus laricio appear to be suitable from 1200 to 2500 m elevation. Taxodium distichum, Pinus radiata, Pinus sabiniana, Pinus pinea and Pinus montezumae have not been found suitable. Only Pinus sylvestris of winter rainfall region has been successful though mortality is high.